Immunotherapy for advanced or metastatic urothelial carcinoma - Maisch, Philipp; Hwang, Eu Chang; Narayan, Vikram; Bakker, Caitlin J.; Kunath, Frank; Dahm, Philipp (Cohrane Library, 2020)
Objectives: This is a protocol for a Cochrane Review (intervention). The objectives are as follows:. To assess the effects of immune checkpoint inhibitors compared to chemotherapy as first- and second-line treatment of advanced or metastatic urothelial carcinoma.
CRIS-Team Scopus Importer:2021-04-19